Economic Valuation of Reducing Submerged Marine Debris in South Korea - Se-Jun Jin; Young-Ju Kwon; Seung-Hoon Yoo (Applied Sciences, 2020)
Submerged marine debris (SMD) scattered between sea level and the bottom of the sea damages the habitats of marine life and threatens its growth in South Korea. The collection of SMD is more difficult and expensive than that of coastal and floating debris. The government is trying to achieve a 33% reduction in SMD by 2023 by expanding its collection, which requires huge additional investments and additional information about the economic value or benefits of the reduction. This article seeks to conduct an economic valuation of the reduction by employing contingent valuation (CV), which asks people to indicate their willingness to pay (WTP) for the reduction. A dichotomous choice CV survey was undertaken with 1000 households by a professional survey firm through person-to-person interviews during July 2019. Overall, people understood the CV questions well and reported the WTP responses for a hypothetical market successfully created with CV. Although 37.9% of interviewees stated zero WTP, the average of the yearly household WTP was estimated as 5523 Korean won (KRW) (USD 4.92). This value ensures statistical significance. The population’s WTP for the reduction would be KRW 110.30 billion (USD 99.75 million) per year over the next five years. It was found that the reduction is socially beneficial since the value was greater than the costs involved in the reduction.